2013
DOI: 10.1016/j.ridd.2013.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Writing to dictation and handwriting performance among Chinese children with dyslexia: Relationships with orthographic knowledge and perceptual-motor skills

Abstract: The purpose of this study was to investigate the relationships between writing to dictation, handwriting, orthographic, and perceptual-motor skills among Chinese children with dyslexia.A cross-sectional design was used. A total of 45 third graders with dyslexia were assessed.Results of stepwise multiple regression models showed that Chinese character naming was the only predictor associated with word dictation (β = .32); handwriting speed was related to deficits in rapid automatic naming (β = -.36) and saccadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 34 publications
4
27
0
2
Order By: Relevance
“…Moreover, children who wrote less fluently turned out to read more slowly, make more errors and have a poorer receptive vocabulary. These results are consistent with those in Cheng-Lai et al (2013), according to which handwriting speed predicted impairments in rapid automatic naming. Finally, our correlation analysis revealed that speed difference between the conditions Big and Spontaneous, which was considered a measure sensitive to children's ability to comply with isochrony, correlated with speed in reading words and non-words, thus supporting the hypothesis that reading and writing are mediated by rhythmic competence.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, children who wrote less fluently turned out to read more slowly, make more errors and have a poorer receptive vocabulary. These results are consistent with those in Cheng-Lai et al (2013), according to which handwriting speed predicted impairments in rapid automatic naming. Finally, our correlation analysis revealed that speed difference between the conditions Big and Spontaneous, which was considered a measure sensitive to children's ability to comply with isochrony, correlated with speed in reading words and non-words, thus supporting the hypothesis that reading and writing are mediated by rhythmic competence.…”
Section: Discussionsupporting
confidence: 89%
“…Overall, these findings support our first hypothesis, which predicted that children with DD with no previous diagnosis of dysgraphia, have some latent handwriting problems, which cannot be attributed to less handwriting practice since children with dyslexia are not relieved of writing responsibilities because of their reading difficulty. They also confirm the findings by Lam et al (2011), which established that speed and accuracy in handwriting could discriminate Chinese children with DD from typically developing children (see also Cheng-Lai et al, 2013). Moreover, our remarks extended to an alphabetic script, which has different requirements from Chinese.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Second, as was shown in the research of Yan et al (2012), handwriting may refine word processes, increase orthographic depth, and make meaning representation of characters more precise. A prior study (Cheng-Lai et al, 2013) demonstrated that the lexical knowledge of Chinese characters plays an important role in individual differences in word dictation performance. Therefore, spelling accuracy is, to some extent, dependent on existing knowledge of vocabulary.…”
Section: Effects Of Handwriting Fluency On Spelling Accuracymentioning
confidence: 99%
“…In contrast to the substantial amount of research examining the direct effects of handwriting fluency and spelling accuracy on writing and reading performance (Graham et al, 1997;Limpo and Alves, 2013), there are only a handful of studies investigating the underlying mechanism of the relationship between handwriting and spelling. By analyzing the influencing factors of spelling accuracy in children in the third grade, researchers (Cheng-Lai et al, 2013) concluded that the degree of difficulty in performing Chinese word dictation covaries with handwriting fluency. However, from a developmental perspective, the bidirectional relationship between handwriting fluency and spelling accuracy remains unclear.…”
Section: Introductionmentioning
confidence: 99%